Simulation of Monsoon Low Pressure System and its Associated Rainfall Over Bangladesh Using WRF Model (Dhaka University Journal of Science, 2018)
In this paper an effort has been made to simulate the monsoon Low Pressure System (LPS) and its associated rainfall event of 16-20 August, 2013 using Weather Research and Forecasting (WRF) model. The model was run for 24-h, 48-h and 72-h in a single domain of 10 km horizontal resolution using The National Centre for Environmental Prediction (NCEP) high-resolution Global Final (FNL) Analysis 6-hourly data using initial and lateral boundary conditions. WRF double-moment 5 class micro physics scheme, Kain–Fritsch (new Eta) cumulus physics scheme,Yonsei University planetary boundary layer scheme, Revised MM5 surface layer physics scheme, Unified Noah LSM as land surface model, Rapid Radiative Transfer Model (RRTM) for long-wave and Dudhia scheme for short-wave scheme are used for the simulation. The performance of the model is evaluated analyzing Mean Sea Level Pressure (MSLP), Wind Pattern, Vorticity, Vertical Wind Shear and Rainfall Distribution. The model successfully captured the low pressure system, initial condition, propagation, landfall time and location reasonably well. The model simulated rainfall amount and associated areas sensibly well compared with the observed data by BMD and Tropical Rainfall Measuring Mission (TRMM).Dhaka Univ. J. Sci. 66(1): 29-35, 2018 (January)